1994
DOI: 10.1063/1.355897
|View full text |Cite
|
Sign up to set email alerts
|

Validity of actinometry to monitor oxygen atom concentration in microwave discharges created by surface wave in O2-N2 mixtures

Abstract: The validity of actinometry to monitor oxygen atom concentration in O2-N2 microwave discharges created by surface wave is investigated. The plasma is created with a gas flow in a quartz tube of inner diameter 16 mm at pressures in the Torr range. First, it is shown that the reliability of actinometry can be deduced from the longitudinal profile of the actinometry signal. Second, absolute concentrations of oxygen atoms are estimated from the experimental actinometry signal and agree satisfactorily with concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 30 publications
6
82
0
1
Order By: Relevance
“…They also found that inclusion of a correction factor for dissociative excitation at lower pressures and currents where the dissociation fraction was found to be < 1% allowed reasonable quantitative results to be obtained for their system. Granier et al [19] applied the method to determine [O] in an O 2 /N 2 microwave surface wave discharge. They monitored atomic oxygen emission at 777 nm and 844 nm in the usual manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that inclusion of a correction factor for dissociative excitation at lower pressures and currents where the dissociation fraction was found to be < 1% allowed reasonable quantitative results to be obtained for their system. Granier et al [19] applied the method to determine [O] in an O 2 /N 2 microwave surface wave discharge. They monitored atomic oxygen emission at 777 nm and 844 nm in the usual manner.…”
Section: Introductionmentioning
confidence: 99%
“…Work done by previous authors has shown that application of the actinometry method does not always yield results that reflect the true atomic oxygen number density in the plasma. The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [1,2,3,4,5] demonstrated that even a small admixture can dramatically change the dissociation of the gas. This phenomenon is generally supposed to be caused by one or more of the following effects: change of reduced electric field E/N in the discharge, various homogeneous reactions or by decrease of the wall recombination coefficient due to heterogeneous reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 17, it is shown that actinometry can be used to monitor the atomic concentration in O 2 and O 2 −N 2 low-pressure ͑67− 266 Pa͒ microwave plasmas.…”
Section: B Optical Diagnosticmentioning
confidence: 99%